Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Produk Scarlett - Merie Novita; I Wayan Suwendra (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine the influence of Product Quality and Price variables on the Purchase Decision of Scarlett products among students of the Economics and Accounting Department at Ganesha University of Education. The population in this study consists of consumers who have purchased Scarlett Whitening products among students of the Economics and Accounting Department. The sample used in this research consisted of 316 students. The sampling technique employed was purposive sampling. Data were collected through the distribution of questionnaires. The analytical techniques used included multiple linear regression analysis and classical assumption tests, which consisted of normality test, multicollinearity test, heteroscedasticity test, linearity test, and hypothesis testing. The results of the study show that: Product Quality partially has a positive and significant effect on Purchase Decision, with a significance value of 0.000 < 0.05. Price partially has a positive and significant effect on Purchase Decision, with a significance value of 0.000 < 0.05. Product Quality and Price simultaneously have a positive and significant effect on Purchase Decision, with a significance value of 0.000 < 0.05.